The Effect Of Sanitation Hygiene Knowledge On Students Clean And Healthy Living Behavior - Nur Maulidiyah; Ratna Palupi Nurfatimah; Nugrahani Astuti; Hanif Naufal Ahmi (Universitas Negeri Padang, 2026)
This investigation was designed to examine the degree to which students' comprehension of sanitation and hygiene principles contributes to the enactment of clean and healthy living behaviors (PHBS) within the framework of food processing practical activities at SMK Dharma Wanita Gresik. The research adopted a quantitative paradigm, integrating a descriptive analytical framework with simple linear regression as the primary inferential technique. A total of 39 students constituted the study population, all of whom were designated as research participants by means of total sampling. Data acquisition was carried out through two standardized instruments, namely a structured knowledge test and a systematic observational checklist. Analysis of the sanitation and hygiene knowledge variable produced a mean value of 9.87 accompanied by a standard deviation of 2.45. The categorical breakdown indicated that 3 students were placed in the very low proficiency level, 12 students in the low level, 10 students in the moderate level, and 14 students in the high knowledge category. Regarding PHBS behavioral enactment, 17 students — representing the largest subgroup — were situated within the low behavioral tier. The very low PHBS category recorded no student placements, while 9 students were assigned to the moderate behavioral level. An additional 8 students were positioned within the good PHBS tier, and 5 students achieved classification at the very good behavioral level. The inferential analysis conducted through simple linear regression demonstrated that students' sanitation and hygiene knowledge failed to produce a statistically significant impact on their PHBS enactment, as substantiated by a p-value of 0.747 and a coefficient of determination (R²) amounting to a mere 0.3%. These results collectively imply that cognitive mastery of sanitation and hygiene principles in isolation functions as a minimal contributor to the formation of clean and healthy behavioral practices during food processing activities, underscoring the likelihood that other contextual variables exert a more substantial role in shaping students' health-related conduct.